Apakah Efektivitas Komite Audit dan Kualitas Audit mempengaruhi Manajemen Laba - Manurung, Roberto; Siagian, Valentine (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
This study was conducted to determine whether the effectiveness of the audit committee and audit quality affect the earnings management of the pharmaceutical sub-sector listed on the IDX. In this research, the data used are the financial statements of 8 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2019. The results of this study indicate that audit committee members do not affect earnings management. Total meetings have an influence on earnings management. Audit quality has an influence on earnings management. The results of all these studies have an influence between the effectiveness of the audit committee with the proportion of the number of committee members and the number of meetings and audit quality on earnings management.